Groundwater externalities of large, surface irrigation transfers: insights from the Godavari-Krishna river link, India - Sharma, Bharat R.; Massuel, S.; Rao, K.V.G.K.; Venot, Jean-Philippe (2009)
The Krishna basin in South India is a fast closing basin. Consumptive water use, mainly for agriculture, accounted for 90.5% of the basin net inflow. The adjoining Godavari basin is comparatively water rich and it is planned to transfer 5325 million m3 of Godavari waters to Krishna through P-V Link. Such a transfer shall make the groundwater-irrigated area more sustainable, a part of the remaining rainfed area will come under irrigation and current benefits shall increase by 65%. MODFLOW results showed groundwater recharge increased by 28% due to supplement irrigation return flow. Annual estimated seepage from the main system was estimated at 183 million m3 per year leading to an average water table rise of 1.83 m. This is also likely to affect 16% of the command with water logging. Integrated planning of surface and groundwater resources and a scientific demand management through optimization of cropping systems have the potential to effectively harness the benefits of the river linking initiative.